Biochemical cualitative characterisation of isolates of Beauveria bassiana of one collection of entomopathogenic fungi from Cenicafé - VALDÉS-DUQUE, BEATRIZ ELENA; VÉLEZ-ARANGO, PATRICIA EUGENIA (Revista Colombiana de Entomología, 1998)
One of the most important aspects in the search of improved strains of entomopathogens to control the coffee berry borer H. hampei (Ferrari), is related to its enzymatic activity and its capacity to take the substrates of the ecosystem, factors that determine the process of virulence of the fungus to the insect and its survival in natural conditions. The collection of entomopathogenic fungi of the Insect Pathology Laboratory at Cenicafé has 93 isolates of the fungus B. bassiana (Bb) from different hosts and geographic regions of the country and outside of it. Those isolates from their original host (HO) and passed through the coffee berry borer (cbb) (RB) are the basis for characterization and selection studies of these biological agents to use in the control of cbb. This work had as the main objective to conduct an enzymatic qualitative evaluation of some isolates of the fungus Bb, HO and RB by using the commercial system api-zym and the solid substrate system, in order to evaluate the effect of the transfer through the cbb on the enzymatic response of the fungus. As a result, 10 isolates of Bb, HO, and RB were taken and cellular suspension of known concentration was prepared in 10% glycerol and kept at -15°C for the enzymatic tests. In general, it was observed that the RB isolates showed a better response in a shorter time of reaction. Consequently, the isolates HO presented some level of activity for 7 of 19 evaluated enzymes in the api-zym commercial system and once passed through the cbb (RB) enzyme activity of 10 of 19 probed enzymes was observed. In the enzymatic evaluation with the solid substrate method it was found that some isolates showed variable response to the chitinase and lipase production. However, after passing these isolates through the cbb, they presented a positive response in the above-mentioned tests. The results confirm the importance of carrying out characterization studies of the isolates once passed through the insect to which the control is directed. This is a criterium of great utility for entities or research centers in which collections of biological agents from a different host and geographic localities are maintained to be characterized and selected in the control of insect pest of crops of economic importance.